Impact of bank holding company affiliation on eirm risk - Jessee, Michael A.; Federal Reserve Bank of New York (New York : Federal Reserve Bank of New York, 1977)
This research paper analyses the behaviour of bank holding companies in terms of their willingness and capacity to assume risk.
Includes bibliographical references
lje 03/05/17
Loans
Keywords: Banks and banking; Bank holding company